An oxygen-sensitive probe and a hydrogel for optical imaging and photodynamic antimicrobial chemotherapy of chronic wounds. (18th March 2022) - Ji, Shilu; Zhou, Sensen; Zhang, Xiaoke; Chen, Weizhi; Jiang, Xiqun
Abstract : Optical probes (Ir-fliq and Ir-fliq-PVP) based on an iridium complex and a hydrogel(CSGI) contained Ir-fliq are designed for hypoxia imaging and antibacterial chemotherapy in this work. Abstract : A small molecular probe (Ir-fliq) and a macromolecular optical probe (Ir-fliq-PVP) based on an iridium complex are designed for hypoxia imaging and antibacterial chemotherapy in this work. The existence of both isoquinoline and fluorene moieties in the probe structure extends the phosphorescence emission to the red-wavelength region. The rigid large conjugated structure of the ligand can also reduce the packing caused by intermolecular interactions and suppress the self-quenching, thus improving the phosphorescence efficiency. The hydrophilic Ir-fliq-PVP has a good ability to generate singlet oxygen and can be used for photodynamic antimicrobial chemotherapy (PACT). Moreover, the small molecular probe Ir-fliq is further cross-linked with carboxymethyl chitosan (CMCS) and sodium alginate (SA) to form a CSGI hydrogel. The biocompatibility, mechanical properties, antibacterial properties and hypoxic imaging ability of the CSGI hydrogel have been evaluated in chronic wound models of diabetic mice. It shows that the CSGI hydrogel can effectively inhibit the growth of bacteria in wounds through PACT under light irradiation, promote the healing of chronic wounds in diabetic mice, and record the hypoxia process of mouse wounds.